Transactions on Large-Scale Data- and Knowledge-Centered Systems XVIII: Special Issue on Database- and Expert-Systems Applications - Hameurlain, Abdelkader; Küng, Josef; Wagner, Roland; Decker, Hendrik; Lhotska, Lenka; Link, Sebastian (Lecture Notes in Computer Science, 2015)
The LNCS journal Transactions on Large-Scale Data- and Knowledge-Centered Systems focuses on data management, knowledge discovery, and knowledge processing, which are core and hot topics in computer science.Since the 1990s, the Internet has become the main driving force behind application development in all domains.